1995
DOI: 10.1017/s0889189300006160
|View full text |Cite
|
Sign up to set email alerts
|

The International Workshop on Establishment of Microbial Inocula in Soils: Cooperative Research Project on Biological Resource Management of the Organization for Economic Cooperation and Development (OECD)

Abstract: Low-input agriculture is likely to be the focal point for future cropping systems. Worldwide there is increasing concern that we must decrease the use of chemicals in agriculture. A leading reason for this concern has been the effects of pesticides on food quality, consumer health, and the environment. There also is concern regarding fertilizers and energy inputs because of environmental pollution from excessive application rates and poor timing of fertilization and because of the depletion of nonrenewable ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 102 publications
0
24
0
1
Order By: Relevance
“…Microbial interactions play very important roles in sustainable agriculture through the integrated nutrient supply [6] . It is important to lay major emphasis on the application of efficient microbial inoculants [4] . Various commercial mono-culture inoculants being produced in India by various government/semi government or private agencies include: A. rhizobia and B. rhizobia, Azospirillum, Azotobacter, Bacillus megaterium, Bacillus polymyxa, mycorrhizal inoculants for forest trees and Pseudomonas as Plant Growth Promoting Rhizobacteria (PGPR) and bio control agent.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial interactions play very important roles in sustainable agriculture through the integrated nutrient supply [6] . It is important to lay major emphasis on the application of efficient microbial inoculants [4] . Various commercial mono-culture inoculants being produced in India by various government/semi government or private agencies include: A. rhizobia and B. rhizobia, Azospirillum, Azotobacter, Bacillus megaterium, Bacillus polymyxa, mycorrhizal inoculants for forest trees and Pseudomonas as Plant Growth Promoting Rhizobacteria (PGPR) and bio control agent.…”
Section: Introductionmentioning
confidence: 99%
“…Actinomycetes inhabit both the rhizoplane and rhizosphere (Solans and Vobis 2003;Frioni 2006) and are known to play some important ecological roles in soil nutrient cycling (Elliot and Lynch 1995), probiotics (Lievin et al 2000), bioremediation (Amoroso et al 2013), nitrogen fixation, and deterioration and decomposition of plant and animal residues and also provide many bioactive compounds such as vitamins, enzymes, and antibiotics (de Boer et al 2005;Busti et al 2006;Prapagdee et al 2008;Genilloud et al 2011). Apart from their beneficial impact, actinomycetes also cause some harmful effects such as they cause diseases and spoil different useful materials (Waksman 1950).…”
Section: Actinomycetes: An Ideal Candidate For Sustainablementioning
confidence: 99%
“…Among these, actinomycetes as P solubilizers (de Vasconcellos et al 2010;Hamdali et al 2012) have been less explored despite showing a better genetic and greater biodiversity potential (Pathom-Aree et al 2006;Thangapandian et al 2007). Also, they represent heterogeneous and abundant microbial populations and hugely affect cycling of nutrient in soil ecosystems (Elliot and Lynch 1995;Figueiredo et al 2010). Recently, the role of actinomycetes in sustainable agriculture (Johansson et al 2004; Strap 2011) via P supply to plants has been identified.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many biocontrol agents only showed impressive control efficacy in suppressing the growth of the pathogen at the laboratory stage, or at best, the glasshouse stage [6] . One of the main reasons for the failure of biocontrol agents to exhibit efficient control is their poor viability in the soil, resulting from soils which are too acidic under water-logged conditions [10] , or due to the intense competition with the indigenous microflora in the soil to establish their own niche and existence in the soil environment.…”
Section: Introductionmentioning
confidence: 99%